2013
DOI: 10.1155/2013/690415
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Small SSEA-4-Positive Putative Stem Cells from the Ovarian Surface Epithelium of Adult Human Ovaries by Two Different Methods

Abstract: The adult ovarian surface epithelium has already been proposed as a source of stem cells and germinal cells in the literature, therefore it has been termed the “germinal epithelium”. At present more studies have confirmed the presence of stem cells expressing markers of pluripotency in adult mammalian ovaries, including humans. The aim of this study was to isolate a population of stem cells, based on the expression of pluripotency-related stage-specific embryonic antigen-4 (SSEA-4) from adult human ovarian sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
63
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(69 citation statements)
references
References 36 publications
(37 reference statements)
6
63
0
Order By: Relevance
“…It is difficult to isolate and grow a large population of cells expressing the markers tested. According to literature reports, human cells of the ovarian surface epithelium (OSE) with an epitope of SSEA-4 demonstrate the expression of stem cell markers such as Oct-3/4, Nanog and Sox-2 [14]. Herein our experiments confirmed that PSCs can be isolated by magnetic beads due to the presence of an epitope SSEA-4 also from the porcine ovary.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…It is difficult to isolate and grow a large population of cells expressing the markers tested. According to literature reports, human cells of the ovarian surface epithelium (OSE) with an epitope of SSEA-4 demonstrate the expression of stem cell markers such as Oct-3/4, Nanog and Sox-2 [14]. Herein our experiments confirmed that PSCs can be isolated by magnetic beads due to the presence of an epitope SSEA-4 also from the porcine ovary.…”
Section: Discussionsupporting
confidence: 82%
“…In normal development, SSEA4 is expressed by the majority of pregonadal primordial germ cells (PGCs) and is progressively downregulated when they enter into meiosis in the embryonic ovary [13]. However, it has been stated that the human SSEA4-positive PSCs from ovarian cell cultures are related to ESCs and cells of the germinal lineage [14].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Virant-Klun's et al (2013) has reported that OSE harbors stem cells, which spontaneously differentiate into oocyte-like structures during in vitro culture. Our group also observed spontaneous differentiation of OSE cells into oocyte-like structures and that the epithelial cells undergo epithelial-mesenchymal transition to form granulosa-like cells that surround the developing germ cells resulting in follicle assembly (Parte et al 2011).…”
Section: R41mentioning
confidence: 89%
“…To elucidate whether the oocytes generated were truly derived from mitotically active PSCs, and did not instead represent oocytes derived from primary ovarian cells, we isolated and purified PSCs by SSEA4-based magnetic bead sorting, as small SSEA4-positive cells from human ovarian cell cultures are reportedly related to ESCs and cells of the germinal lineage (Virant-Klun et al, 2013), and small porcine PSCs showed cytoplasmic expression of SSEA4 (supplementary material Fig. S4A).…”
Section: Arrows) (C) After 2 Weeks Thementioning
confidence: 99%